2014
DOI: 10.7567/apex.7.082302
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of MgF2as a back reflector in a-SiOx:H thin-film solar cells

Abstract: We present high-quality a-SiOx:H solar cells with a very thin i-layer of 100 nm fabricated at a low temperature of 100 °C. To boost the photocurrent with such a thin absorber, we suggested the application of a low-index MgF2 buffer at the n-type nanocrystalline silicon oxide (n-nc-SiOx:H)/Ag nanotextured interface to suppress the absorption loss at the Ag back contact. The introduction of MgF2 of only a few nanometers (∼4 nm) thickness enhanced the reflection at the n-nc-SiOx:H/Ag interface, which resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Also, in order to obtain high open‐circuit voltage, wide‐bandgap a‐SiO:H that we have developed so far is used for 1st, 2nd, 4th and 5th cells . Low temperature deposited a‐Si:H is used for the 3rd cell.…”
Section: Structure and Fabrication Methods Of Amorphous Si:h Based Quimentioning
confidence: 99%
“…Also, in order to obtain high open‐circuit voltage, wide‐bandgap a‐SiO:H that we have developed so far is used for 1st, 2nd, 4th and 5th cells . Low temperature deposited a‐Si:H is used for the 3rd cell.…”
Section: Structure and Fabrication Methods Of Amorphous Si:h Based Quimentioning
confidence: 99%
“…In the case of intrinsic a-SiO x :H films, the deposition rate was $ 2.3 nm/min with a bandgap of 1.85 eV (from Tauc's plot). Other deposition environments were described in detail in previous studies [18]. A magnetron sputtering system was used to prepare AZO thin films for the back reflection.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the optical losses of the back reflector can also be reduced by introducing magnesium fluoride (MgF 2 ) or lithium fluoride (LiF) as a buffer layer in thin film [42,43] and crystalline silicon heterojunction solar cells [44]. Both materials exhibit a low refractive index (n o1.5) and a very low extinction coefficient.…”
Section: Enhancing the Short Circuit Current And Minimizing Optical Lmentioning
confidence: 98%